Фармакоепідеміологічна та фармакоекономічна оцінка лікування хворих на цукровий діабет - Яковлева, Л. В.; Кириченко, О. Н. (Clinical Endocrinology and Endocrine Surgery, 2011)
The review deals the results of comparative studies of pharmacoeconomic efficacy of drugs for insulin replacement therapy – genetically engineered prolonged human insulin and analogs of human insulin of nonpeak action (glargine, detemir). Evidence of high economic effectiveness of insulin glargine is shown. The need to conduct clinical and economic studies of insulin glargine in Ukraine and the establishment of national economic criteria for eligibility of additional costs are indicated.